Low-voltage gradient zinc oxide voltage-sensitive ceramic as well as preparation method and application thereof
By introducing superhard nanosecond phase materials into zinc oxide ceramics and adopting cold sintering process to adjust the internal stress of the ceramics, the problem of insufficient nonlinear response at low voltage is solved, and high-efficiency nonlinear current-voltage response under low voltage gradient is achieved.
Patent Information
- Application Number
- CN202411541992.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The nonlinear current-voltage response shown by existing zinc oxide ceramics at low voltages is insufficient, making it difficult to meet the demand of varistors under low voltage conditions.
By introducing superhard nanosecond phase materials, such as nanodiamond, into zinc oxide ceramics, and using a cold sintering process, local residual stress is introduced to adjust the internal stress of the ceramics, thereby improving its nonlinear response at low voltages.
It is achieved to significantly improve the nonlinear current-voltage response of zinc oxide pressure-sensitive ceramics under low voltage gradients, reduce the varistive voltage, and improve the stability of the ceramics.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and particularly relates to a low-voltage gradient zinc oxide varistor ceramic and a preparation method and application thereof. Background Art
[0002] Due to the rapid development of integrated circuits and semiconductor electronics, the demand for low-voltage varistors has become stronger in recent years. In order to greatly reduce the varistor voltage in the varistor, ceramics with exaggerated growth grains must usually be made as thin as possible. However, the thin-layer design of zinc oxide ceramics not only leads to increased sensitivity to the microstructure because there are few grain boundaries along the electric field, but also the risk of mechanical failure increases as the thickness decreases.
[0003] Therefore, it is desirable to find an alternative strategy to design the barrier in low-voltage varistors. In addition to the contribution of dopants, it has long been recognized that the piezoelectric effect plays an important role due to the non-centrosymmetric wurtzite structure of ZnO. However, this effect is usually negligible for most ZnO-based varistors due to the small internal stress generated by high-temperature sintering. In contrast, experiments on ZnO-based bicrystals with predetermined polarization vectors have shown that large external compressive stress can greatly reduce the barrier height in the head-to-heat direction along the c-axis vector, while increasing the barrier height in the tail-to-tail direction. Although these findings indicate the potential of piezoelectric devices, in practice, regulating the barrier by internal stress is more desirable because varistors are rarely subjected to large external mechanical loads. In fact, early studies have shown that internal thermal stress can affect the distribution of barrier heights, but the change in the current-voltage response is very limited compared to the response under external load.
[0004] Therefore, a simple and efficient strategy is provided to adjust the internal stress in ZnO (including doped and undoped) ceramics to achieve a significant nonlinear current-voltage response at low voltage, which is very important for varistor ceramic materials. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a low voltage gradient zinc oxide varistor ceramic and a preparation method and application thereof.
[0006] The invention provides a zinc oxide varistor ceramic. The zinc oxide varistor ceramic comprises 90-100 parts of zinc oxide and 0-6 parts of a second phase material in parts by weight.
[0007] Preferably, the zinc oxide varistor ceramic component includes 94-98 parts of zinc oxide and 2-6 parts of the second phase material by weight.
[0008] Preferably, the zinc oxide is undoped zinc oxide or doped zinc oxide, and the doped zinc oxide includes one or more doped zinc oxides selected from Co, Al, Mn, Cr, etc.;
[0009] Further preferably, the zinc oxide is a nanomaterial.
[0010] The second phase material is a hard second phase material, wherein the elastic modulus is above 300 GPa.
[0011] Preferably, the second phase material includes at least one of nanodiamond, α-phase alumina, cubic boron nitride and other second phases with an elastic modulus higher than 300 GPa.
[0012] Furthermore, the nanodiamond is unmodified nanodiamond or acid-modified nanodiamond.
[0013] The acid-modified nanodiamond is a nanodiamond modified with a mixed acid of concentrated sulfuric acid (H2SO4) and concentrated nitric acid (HNO3).
[0014] The preparation method comprises: mixing a mixture of nano-diamond, concentrated sulfuric acid (H2SO4) and concentrated nitric acid (HNO3), and reacting the mixture by ultrasonication and water bath stirring for 2-10 hours to obtain the nano-diamond.
[0015] The zinc oxide varistor ceramic is obtained by cold sintering a raw material containing zinc oxide and a second phase material.
[0016] The zinc oxide varistor ceramic is a low voltage gradient zinc oxide varistor ceramic, wherein the varistor voltage is below 100 V / mm, and further is 10 V / mm-50 V / mm.
[0017] The present invention provides a method for preparing a zinc oxide varistor ceramic, comprising:
[0018] The components are weighed according to their weight proportions, and the mixture containing zinc oxide and the second phase material is sintered to obtain zinc oxide varistor ceramics.
[0019] The zinc oxide includes but is not limited to zinc oxide powder; the second phase material includes but is not limited to hard second phase powder.
[0020] Preferably, the preparation of the mixture containing zinc oxide and the second phase material comprises method 1 or method 2;
[0021] The method 1 includes mixing zinc oxide and water, and then mixing with a second phase material solution, filtering and collecting the precipitate, and drying to obtain a mixture;
[0022] The method 2: zinc oxide, the second phase material and a solvent are mixed, ball-milled and dried to obtain a mixture.
[0023] Furthermore, in the method 1, zinc oxide and water are mixed, stirred, and ultrasonically treated to form a stable ZnO colloidal solution, the second phase material is dispersed in water, and the well-dispersed ZnO colloidal solution is dropped under magnetic stirring, the second phase material and zinc oxide powder quickly self-assemble and precipitate to the bottom, and the precipitated second phase material / zinc oxide mixture is collected by vacuum filtration and dried.
[0024] Preferably, in the method 1, the zinc oxide and water are mixed, stirred, and ultrasonicated for 0.5-1.5h;
[0025] In method 1, the concentration of zinc oxide and water after mixing is 5-20 mg / mL;
[0026] In the method 1, the concentration of the second phase material solution is 0.5-2 mg / mL; the solvent of the second phase material solution is water;
[0027] The drying in the method 1 is vacuum drying at a temperature of 60-100° C. for a time of 12-24 hours.
[0028] Preferably, the solvent in method 2 is ethanol; the ball milling parameters in method 2 include: the ball-to-material ratio of ball milling is 40-60:1, the ball milling speed is 100-200 r / min, and the ball milling time is 3-8 h; the drying temperature is 80-120° C., and the drying time is 4-8 h.
[0029] The mixture containing zinc oxide and the second phase material is mixed evenly, wherein the mixing method is such as grinding.
[0030] Furthermore, the grinding of the mixture containing zinc oxide and the second phase material comprises: mixing the mixture of zinc oxide and the second phase material with acetic acid and then grinding; wherein the concentration of the acetic acid is 0.6M-2M; and the mass ratio of the acetic acid to the mixture is 15-20:100;
[0031] Preferably, the grinding time is 3-10 hours.
[0032] Preferably, the sintering is cold sintering, wherein the cold sintering process parameters are: uniaxial pressure 50-300 MPa, heating rate 10-30° C. / min, sintering temperature 100-400° C., and time 0.5-6 h.
[0033] Cold sintering was carried out in a stainless steel mold and uniaxial pressure was applied.
[0034] The present invention provides a zinc oxide varistor with a low voltage gradient or a zinc oxide varistor with a low voltage gradient prepared by the method, which has applications in the fields of integrated circuits, semiconductor electronics, automotive electronics, communication equipment, etc., and has a protection circuit to improve its stability, prevent overvoltage, and maintain normal operation of the system.
[0035] In the present invention, ultra-hard nano second phase particles are introduced through a cold sintering process, which can generate large local residual stress in the ZnO matrix. The grain boundary barrier of the ZnO-based low-voltage varistor is adjusted by utilizing the piezoelectric polarization induced by the built-in stress. In addition, the present invention can effectively control the varistor voltage of undoped and doped varistor ceramics by adjusting the sintering pressure and the content of the second phase, and obtain a low voltage gradient ZnO varistor ceramic.
[0036] Beneficial Effects
[0037] The present invention uses zinc oxide and a second phase to composite, and an effective strategy to adjust the ZnO-based low-voltage varistor barrier by utilizing internal stress-induced piezoelectric polarization. The introduction of a superhard second phase through a sintering process can generate local residual stresses up to 1 GPa in the ZnO matrix. Therefore, the superhard second phase / zinc oxide composite material exhibits a significant nonlinear current-voltage response at low varistor voltage, which is attributed to the significant effect of positive and negative polarization on the grain boundary barrier, causing the barrier height to decrease.
[0038] The low voltage gradient ZnO varistor provided by the present invention can achieve effective regulation of the varistor voltage of undoped and doped ceramics by adjusting the sintering pressure and the content of the second phase, thereby obtaining different low voltage gradient ZnO varistor ceramics.
[0039] For example, by comparing Example 1 with Example 3, the content of the second phase is adjusted to obtain different low voltage gradient ZnO varistors.
[0040] For example, by comparing Example 3 with Example 5, different low voltage gradient ZnO varistor ceramics are obtained by adjusting the sintering pressure.
[0041] The low voltage gradient ZnO varistor ceramic provided by the present invention has a varistor voltage of less than 100V / mm (10V / mm-50V / mm) and a nonlinear coefficient of 4-40. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a scanning electron microscope image of a cross section of a zinc oxide block prepared in Comparative Example 1 of the present invention;
[0043] Figure 2 is a scanning electron microscope image of a cross section of a diamond / zinc oxide composite material block prepared in Example 1 of the present invention;
[0044] Figure 3 This is a transmission electron microscope image of a bulk of a nano-diamond / zinc oxide composite material prepared in Example 1 of the present invention;
[0045] Figure 4 a is the Raman spectra of the samples of Example 1 and Comparative Example 2 of the present invention and Figure 4 b is the X-ray diffraction pattern of the samples of Example 1 and Comparative Example 2 of the present invention;
[0046] Figure 5 Graphs showing the electric field E and current density J of the embodiments of the present invention and the comparative example. DETAILED DESCRIPTION
[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0048] 1. Materials Table 1 shows the specifications and sources of the raw materials or reagents used in the examples of the present invention.
[0049] Material Name Specifications (purity) Manufacturer (Origin) Nano zinc oxide 99.99% Shanghai MacLean Biochemical Technology Co., Ltd. Co-doped nano zinc oxide 99.99% China National Pharmaceutical Group Shanghai Reagent Company Zinc oxide ZnO (Example 2 only) ≥99.0% China National Pharmaceutical Group Shanghai Reagent Company Nanodiamond (elastic modulus 980GPa) 99.99% Henan Yuxing Carbon Materials <![CDATA[C 60 (Elastic modulus 36GPa)]]> 99.99% Shanghai MacLean Biochemical Technology Co., Ltd. Anhydrous ethanol 99.9% China National Pharmaceutical Group Shanghai Reagent Company Commercial α-phase alumina powder (elastic modulus 400GPa) 99.99% Japan Daimei Industry Co., Ltd. Nitric acid 63~65% China National Pharmaceutical Group Shanghai Reagent Company sulfuric acid 95~98% China National Pharmaceutical Group Shanghai Reagent Company
[0050] In the embodiment and the comparative example, the samples were sprayed with gold on both sides, and the nonlinear performance was tested by a varistor tester. The test method was as follows: the samples were tested by the varistor tester at a given 0.01 mA / mm 2 and 0.1mA / mm 2 Voltage value when current is and Will Recorded as the varistor voltage, and then use and The nonlinear coefficient α is calculated by formula 1:
[0051]
[0052] Example 1
[0053] (1) To prepare the acid-treated nanodiamonds, 1 g of nanodiamond particles were placed in a three-necked flask and mixed with 100 ml of a concentrated acid solution of 98% sulfuric acid (H2SO4) and 68% nitric acid (HNO3) in a volume ratio of 3:1. The mixture was placed in an ultrasonic bath for 30 minutes and then vigorously stirred in an 80°C water bath for 4 hours. After cooling to room temperature, 200 ml of deionized water was added to dilute the mixture. The obtained diamond particles were repeatedly washed with a large amount of deionized water by vacuum filtration until the pH value became neutral. Finally, the nanodiamond particles were dried at 80°C for 12 hours. Acid-treated diamonds were obtained.
[0054] (2) First, pour the nano zinc oxide powder into deionized water and stir for half an hour, then ultrasonicate for 1 hour to form a stable zinc oxide colloidal solution. Secondly, disperse the acid-treated nano diamond in deionized water (0.5 mg / ml) and drop the well-dispersed zinc oxide colloidal solution under magnetic stirring. The nano diamond and zinc oxide powder quickly self-assemble and precipitate to the bottom. The precipitated nano diamond and zinc oxide mixture is collected by vacuum filtration and dried in a vacuum oven at 60°C for 24 hours to obtain a mixed powder (ZnO and nano diamond with a mass ratio of 96:4).
[0055] (3) Mix the powder with 20% of its total mass of 0.6 mol L -1 The acetic acid and aqueous solution were mixed and ground with a mortar and pestle for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 150 MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15 ° C / min and was kept at 300 ° C for 60 minutes. After sintering, the block was naturally cooled to room temperature. Its varistor voltage is 25.7 V / mm and the nonlinear coefficient is 8.1.
[0056] like Figure 2 The figure shows: a scanning electron microscope image of a cross section of a block of a diamond / zinc oxide composite material prepared in Example 1 of the present invention, in which shiny diamonds are distributed in a zinc oxide matrix.
[0057] like Figure 3 The figure shows: a transmission electron microscope image of a block section of the diamond / zinc oxide composite material prepared in Example 1 of the present invention, in which diamonds are distributed in the zinc oxide matrix.
[0058] like Figure 4 a and Figure 4 As shown in b, the Raman spectra of the samples of Example 1 and Comparative Example 2 of the present invention show that the diamond in Example 1 does not undergo phase change, while the diamond in Comparative Example 2 undergoes phase change.
[0059] like Figure 5 The electric field E and current density J of the embodiments of the present invention and the comparative example are shown in the figure. By adding the superhard second phase, the varistor voltage of the zinc oxide matrix of the embodiments 1, 2, and 3 of the present invention is lower than that of the comparative example 1.
[0060] Example 2
[0061] (1) ZnO and α-phase Al2O3 in a mass ratio of 96:4 were mixed and then anhydrous ethanol was added to obtain a slurry, the slurry was placed in a ball mill at a speed of 150 r / min for 5 h, the ball-to-material ratio of the ball milling was 50:1, and then dried at 80°C for 8 h to obtain a mixture;
[0062] (2) Mix the powder with 20% of its total mass of 0.6 mol L-1 The acetic acid aqueous solution was mixed and ground with a mortar for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 150MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15℃ / min and was kept at 300℃ for 60 minutes. After sintering, the block was naturally cooled to room temperature. Its varistor is 35.4V / mm and the nonlinear coefficient is 4.9.
[0063] Example 3
[0064] According to Example 1, step (1) of this example is the same as step (2) in Example 1 (ZnO and nanodiamond in a mass ratio of 98:2).
[0065] (2) Mix the powder with 20% of its total mass of 0.6 mol L -1 The acetic acid aqueous solution was mixed and ground in a mortar for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 150 MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15 °C / min -1 , and kept at 300℃ for 60 minutes. After sintering, the block was cooled naturally to room temperature. Its varistor voltage is 15.7V / mm and the nonlinear coefficient is 5.4.
[0066] like Figure 5 The figure shows: the electric field E and the current density J of the embodiment of the present invention and the comparative example. By adjusting the content of the second phase, different low voltage gradient ZnO varistor ceramics are obtained in embodiment 1 and embodiment 3.
[0067] Example 4
[0068] According to Example 1, step (1) of this example is the same as step (2) in Example 1 (Co-doped zinc oxide and nano-diamond in a mass ratio of 97:3).
[0069] (2) Mix the powder with 18% of its total mass of 1 mol L -1 The acetic acid and aqueous solution were mixed and ground with a mortar and pestle for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 150 MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15 ° C / min and was kept at 300 ° C for 60 minutes. After sintering, the block was naturally cooled to room temperature. Its varistor voltage is 19.2 V / mm and the nonlinear coefficient is 12.4.
[0070] Example 5
[0071] According to Example 1, step (2) of this example is the same as that of Example 1 (ZnO and nanodiamond in a mass ratio of 98:2).
[0072] (2) Mix the powder with 20% of its total mass of 0.6 mol L -1 The acetic acid aqueous solution was mixed and ground in a mortar for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 100 MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15 °C / min -1 , and kept at 300℃ for 60 minutes. After sintering, the block was cooled naturally to room temperature. Its varistor voltage is 20.3V / mm and the nonlinear coefficient is 5.1.
[0073] Comparative Example 1
[0074] 0.6 mol L of nano zinc oxide and 20% of its total mass -1 The acetic acid aqueous solution was mixed and ground in a mortar for 6 minutes. Subsequently, the wet powder was loaded into a stainless steel mold and a uniaxial pressure of 150 MPa was applied. The heating jacket integrated with the mold gave a heating rate of 15 °C / min -1 , and kept at 300℃ for 60 minutes. The varistor voltage is 102.3V / mm, and the nonlinear coefficient is 1.2.
[0075] like Figure 1 The figure shows that the SEM image of the cross section of the zinc oxide block prepared in Comparative Example 1 of the present invention shows that the grains are larger than those in Example 1. Figure 2 In, display Figure 2 Shiny diamond particles.
[0076] Comparative Example 2
[0077] The mixed powder of Example 1 is different only in that the discharge plasma is used, and the process parameters are as follows: sintering temperature is 950°C, heating rate is 100°C / min, holding time is 8min, the mold is a graphite mold, the varistor voltage is 140V / mm, and the nonlinear coefficient is 1.1.
[0078] Comparative Example 3
[0079] The mass ratio of nano zinc oxide and C 60 The mixed powder (elastic modulus is about 36 GPa) is sintered according to step (3) in Example 1, and its varistor voltage is 1400 V / mm and the nonlinear coefficient is 6.2.
[0080] In Example 1 of the present invention, a superhard second phase diamond (980GPa>300GPa) is added to the zinc oxide powder and sintered into a block, and in Comparative Example 3, a soft second phase C is added to the zinc oxide powder. 60(36GPa<300GPa) sintered into blocks. The two are in sharp contrast. The varistor voltage of Example 1 is 25.7V / mm, while the varistor voltage of Comparative Example 3 is as high as 1400V / mm, which forms a sharp contrast, reflecting that the introduction of the superhard second phase through the sintering process produces a local residual stress of up to 1GPa in the ZnO matrix. This causes the piezoelectric polarization of zinc oxide, thereby reducing the barrier height. Therefore, the superhard second phase / zinc oxide composite material exhibits a significant nonlinear current-voltage response at low varistor voltage.
Claims
1. A zinc oxide varistor ceramic, characterized in that: In terms of weight, the zinc oxide varistor ceramic components include 90-100 parts of zinc oxide and 0-6 parts of the second phase material.
2. The zinc oxide varistor ceramic according to claim 1, characterized in that: In terms of weight, the zinc oxide varistor ceramic components include 94-98 parts of zinc oxide and 2-6 parts of the second phase material.
3. The zinc oxide varistor ceramic according to claim 1, characterized in that: The second phase material is a hard second phase material, wherein the elastic modulus is above 300 GPa; The zinc oxide is undoped zinc oxide or doped zinc oxide.
4. The zinc oxide varistor ceramic according to claim 3, characterized in that: The doped zinc oxide includes one or more of Co, Al, Mn and Cr; The hard second phase material includes at least one of nano diamond, α-phase aluminum oxide, and cubic boron nitride.
5. A method for preparing a zinc oxide varistor ceramic, comprising: The components are weighed according to their weight proportions, and the mixture containing zinc oxide and the second phase material is sintered to obtain zinc oxide varistor ceramics.
6. The preparation method according to claim 5, characterized in that: The preparation of the mixture containing zinc oxide and the second phase material includes method 1 or method 2; The method 1 includes mixing zinc oxide and water, and then mixing with a second phase material solution, filtering and collecting a precipitate, and drying to obtain a mixture; The method 2: zinc oxide, the second phase material and a solvent are mixed, ball-milled and dried to obtain a mixture.
7. The preparation method according to claim 6, characterized in that: In the method 1, zinc oxide and water are mixed, stirred, and ultrasonicated for 0.5-1.5h; In method 1, the concentration of zinc oxide and water after mixing is 5-20 mg / mL; In the method 1, the concentration of the second phase material solution is 0.5-2 mg / mL; the solvent of the second phase material solution is water; The drying in the method 1 is vacuum drying at a temperature of 60-100° C. for a time of 12-24 hours.
8. The preparation method according to claim 6, characterized in that: In the method 2, the solvent is ethanol; The ball milling parameters in the method 2 include: a ball-to-material ratio of 40 to 60:1, a ball milling speed of 100 to 200 r / min, and a ball milling time of 3 to 8 hours; the drying temperature is 80 to 120° C., and the drying time is 4 to 8 hours.
9. The preparation method according to claim 5, characterized in that: The grinding of the mixture containing zinc oxide and the second phase material comprises: mixing the mixture of zinc oxide and the second phase material with acetic acid and then grinding; wherein the concentration of the acetic acid is 0.6M-2M; and the mass ratio of the acetic acid to the mixture is 15-20:100; The grinding time is 3-10h.
10. The zinc oxide varistor ceramic according to claim 1, characterized in that: The sintering is cold sintering; the cold sintering process parameters are: uniaxial pressure 50-300MPa, heating rate 10-30°C / min, sintering temperature 100-400°C, and time 0.5-6h.
11. Application of the low voltage gradient zinc oxide varistor ceramic according to claim 1 or the low voltage gradient zinc oxide varistor ceramic prepared by the method according to claim 5 in the fields of integrated circuits, semiconductor electronics, automotive electronics, and communication equipment.
Citation Information
Patent Citations
Preparation method of modified zinc oxide-type pressure-sensitive ceramic material
CN108706970A
High-potential-gradient ZnO voltage-sensitive ceramic based on cold sintering and preparation method thereof
CN111848152A
Manufacture of zinc oxide varistor
JP1990012901A
varistor
US20090021341A1